2016
DOI: 10.31234/osf.io/cpv3s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-linguistic relations between quantifiers and numerals in language acquisition: Evidence from Japanese

Abstract: A study of 104 Japanese-speaking 2- to 5-year-olds tested the relationbetween numeral and quantifier acquisition. Experiment 1 assessed Japanesechildren’s comprehension of quantifiers, numerals, and classifiers.Relative to English-speaking counterparts, Japanese children were delayedin numeral comprehension at 2 years old, but showed no difference at 3 and4. Also, Japanese 2-year-olds had better comprehension of quantifiers,indicating that their delay was specific to numerals. A second studyexamined the speech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 14 publications
(28 reference statements)
1
29
0
Order By: Relevance
“…The major difficulty for the nativist position is the fact that acquisition of number words (or numerals) by children takes a long time, completed only at the age of three and a half to four years. Experimental results documenting this protracted learning process have been replicated since Wynn's (1992) longitudinal study (Barner et al 2009;Le Corre & Carey 2007;Le Corre et al 2006;Sarnecka et al 2007). Gelman and Gallistel (1978) propose in their seminal work on children's numerical abilities that various innate principles underlie our ability to count.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…The major difficulty for the nativist position is the fact that acquisition of number words (or numerals) by children takes a long time, completed only at the age of three and a half to four years. Experimental results documenting this protracted learning process have been replicated since Wynn's (1992) longitudinal study (Barner et al 2009;Le Corre & Carey 2007;Le Corre et al 2006;Sarnecka et al 2007). Gelman and Gallistel (1978) propose in their seminal work on children's numerical abilities that various innate principles underlie our ability to count.…”
Section: Introductionmentioning
confidence: 55%
“…Sarnecka et al (2007) observe that Japanese children lag behind compared with English and Russian learners at an early stage of numeral acquisition, though Barner et al (2009) have shown that they soon catch up. As a possible factor that causes the initial delay, Barner et al point to the morphological complexity of numerals due to the presence of a classifier.…”
Section: Aspects Of Development Explainedmentioning
confidence: 99%
See 1 more Smart Citation
“…These number-knower levels are found in children acquiring number systems not only in English, but also in Arabic, Japanese, Mandarin Chinese, Russian, Slovenian, and even among the Tsimane', a farming and foraging society in rural Bolivia (Almoammer et al, 2013;Barner, Libenson, Cheung, & Takasaki, 2009;Li, Le Corre, Shui, Jia, & Carey, 2003;Piantadosi, Jara-Ettinger, & Gibson, 2014;Sarnecka, Kamenskaya, Yamana, Ogura, & Yudovina, 2007).…”
Section: Acquiring a System Of Representation For Exact Numbersmentioning
confidence: 99%
“…This account would need to explain why iota was maturationally delayed, when no such delay was observed with other complex logical representations like those associated with quantifiers like all (which emerge much earlier in acquisition; see Barner et al 2009aBarner et al , 2009b). In our view, an account that appeals to maturation has difficulty explaining differences in the acquisition trajectories of different logical forms, particularly when these representations are equivalently complex, frequent in language, and fundamental to linguistic meaning.…”
Section: Maturation Of Semantic or Conceptual Resourcesmentioning
confidence: 99%